Effect of direct sowing system on soil properties and irrigation water use in corn (Zea mays L.) in Sinaloa, Mexico - Sifuentes Ibarra, Ernesto; Macías Cervantes, Jaime; Mendoza Pérez, Cándido; Vázquez Díaz, David Alejandro; Salinas Verduzco, Daniel Arturo; Inzunza Ibarra, Marco Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
Sinaloa is the main producer of corn nationwide, however, excessive tillage and the practice of monoculture corn for more than 30 years, have caused loss of soil fertility, lower water retention and increased production costs. In order to evaluate the effect of the direct seeding system (SD) on the physical-chemical properties of the soil and on the water use efficiency of the corn crop, a study was conducted in the north of Sinaloa, Mexico for three years agricultural cycles under sprinkler irrigation (central pivot), where the treatments were established 1) SD; and 2) conventional tillage of the region (LC) in 0.5 ha each. The properties of the soil evaluated were organic matter (MO), bulk density (Da), total porosity (E), pH and electrical conductivity (CE). In addition, two fixed stations with sensors were installed at three depths of the profile (30, 60 and 90 cm) to measure the behavior of usable humidity (HA) and soil temperature (Ts). The results showed that in the third cycle the organic matter reached a value of 1.47% in SD, while in LC it remained 1%, the pH and the CE showed slight decrease. It was also observed in SD greater stability of humidity in the soil profile, with an increase of 4.62% of HA and a reduction of 1 oC of Ts, which allowed to eliminate an irrigation of relief that represents a saving of 800 m3 ha-1. The elimination of this irrigation and the work of preparing the land and controlling weeds reduced production costs by 20%.
Keywords: water saving, climate change, cost reduction, soil improvement